(untitled) (Gaceta Técnica, 2017)
In the Pre-school of the Simón Bolívar Educational Unit, of the Juan José Mora municipality of the Carabobo State, Venezuela, the Corrosion failure symptom and the Environmental Classification were analyzed according to the Concrete norm: Durability NTF 4015-12. Faults in structural and non-structural elements were studied based on information obtained through visual inspection and interviews with teaching staff. To facilitate the study, it was sub-divided into two modules, and a structural system of reinforced concrete was observed, designed and constructed in various periods, which depended on the needs and sponsorship of other public entities (1959 and 1991). The environment was classified as M4 type, since the identified faults and their most probable causes depended mostly on the marine environment, rather than on the industrial environment.